Lack of Cultural Competency in International Aid Responses: The Ebola Outbreak in Liberia - Southall, Hannah Grace; DeYoung, Sarah E.; Harris, Curt Andrew (Frontiers in Public Health, 2017)
A cornerstone of effective disaster management is that response should always begin and end at the local level (1). The response to the Ebola Virus Disease (EVD) outbreak in Liberia, West Africa, was a combination of independent efforts by many nations and organizations. Many of these independent efforts ignored or were not able to work with the local levels of emergency management in Liberia. This oversight occurred because of the Liberian’s mistrust of both their government and foreign aid groups, as well as the lack of cultural competency demonstrated by the aid groups. The healthcare and emergency management infrastructure in Liberia appeared to be nonexistent at the beginning of the EVD outbreak. However, there were resources available at the community level: The Liberians and their culture. Although these resources were rarely used, there were some instances in which communities were included in response efforts. It was in these instances that possible improvements to international disaster response protocol were found.